Early and phased retirement in European companies establishment survey on working time 2004-2005 - Leber, Ute. (Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2007)
In order to comply with the resolutions of the European Council of 2001, the aims of which include increasing the employment rate among people aged 55-64 years and the average retirement age, EU countries are currently discussing strategies designed to meet these objectives. As the European Commission's report, Employment in Europe 2006, shows, while nearly all Member States increased employment rates for older workers between 2000 and 2005, there remains a significant shortfall in relation to the 50% target at EU level. Since the timing and the nature of the transition into retirement are influenced by the legal framework within the different countries, early and phased retirement schemes play an important role in this context.